The Relationship Between Curriculum, Pedagogy, Andragogy, and Assessment in the Competence-Based Education and Training in Ugandan Higher Education Context: An Empirical Review - Angela, Geoffrey; Kansiime, Margaret Lubega; Amongi, Lydia (British Journal of Contemporary Education, 2026)
Introduction: Competence-based education and training (CBET) has been widely embraced in Ugandan higher education to tackle concerns about graduate employability and skills gaps. However, the extent to which curriculum design, pedagogy/andragogy, and assessment are coherently aligned to foster competency development remains uncertain. Methods: An empirical review approach was employed to synthesise findings from qualitative and quantitative studies, policy documents, and institutional reports on CBET in Ugandan higher education and related East African contexts. Evidence was organised across four domains: curriculum, pedagogy/andragogy, assessment, and implementation outcomes, with particular focus on health professions, teacher education, and selected professional programmes. Results: The review reveals significant progress in defining competency frameworks and restructuring curricula around clear outcomes. Practice-oriented pedagogies, such as clinical placements, role-plays, and project-based learning, are increasingly adopted but remain constrained by large class sizes, resource shortages, and insufficient staff training. Assessment reforms include greater utilisation of criterion-referenced, formative, and scenario-based approaches, though high-stakes written examinations still predominate in many programmes. Alignment among curriculum, pedagogy/andragogy, and assessment is strongest where institutions invest in faculty development and structured workplace-based learning and weakest in under-resourced settings and emerging disciplines. Key findings: First, curriculum reform alone does not ensure competency development; its success depends on congruent pedagogical and assessment practices. Second, andragogical principles, feedback, self-monitoring, and authentic tasks are most effective when integrated into systematic assessment frameworks. Third, gaps in teacher/lecturer assessment literacy and unequal resource distribution hinder consistent CBET implementation and aggravate institutional inequalities. Conclusion: CBET in Ugandan higher education has shifted discourse and formal curricula towards competencies, but implementation remains partial and uneven. Misalignment between curriculum goals, teaching practices, and assessment systems hampers the realisation of intended graduate competencies. Recommendations: The study advocates for sustained investment in staff development programmes focused on competency-oriented pedagogy and assessment, the development and refinement of discipline-specific competency frameworks, enhancement of criterion-referenced and workplace-based assessment systems, better resourcing of learning environments, and closer vertical alignment between secondary and higher education to facilitate coherent competence progression.
Keywords: Competence-Based Education and Training (CBET); Higher Education Institutions (HEIs); Curriculum Implementation; Pedagogy and Andragogy; Assessment Practices; Student Enrolment and Registration; Uganda Higher Education Context.